A bio-inspired novel active elastic component based on negative Poisson's ratio structure and dielectric elastomer - Wang, Yuanlong; Zhao, Wanzhong; Wang, Huaming; Liu, Zhi (Smart materials and structures, 2019)
Dielectric elastomer is one of the most concerned type of electroactive polymer. When a membrane of dielectric elastomer is subject to a voltage on both sides, the membrane reduces thickness and expands area, and vice versa. Due to this unique behavior, dielectric elastomer can be applied as active structure, actuator, sensor, energy harvesting component, etc. However, the mechanical performance of active structure is limited by the low Young's modulus of dielectric elastomer. Inspired by the human's bone-muscle system, a novel active structure that applying dielectric elastomer on the double-V type Negative Poisson's ratio (NPR) structure was proposed in this paper. When voltage and load vary, mechanical performance and dimensions of proposed Electroactive NPR (ENPR) structure change. The electro-mechanical model of ENPR structure was established from the perspective of Helmholtz free energy. And the theoretical model was verified by the experiment of an ENPR structure prototype. Furthermore, the influences of dimensions of dielectric elastomer and structural parameters on the electro-mechanical performance were researched. The results indicated that all variables influenced the stiffness of ENPR structure. Width L 2 , number of cells n x and number of layers n y had limited effects on the electroactive response, but tuning of others variables which can improve stiffness will weaken the electroactive response. Through periodic replication of ENPR cells, the electro-mechanical property can be superimposed to satisfy higher bearing requirements and larger size demands. ENPR structure can realize integration, electronization, informatization and intellectualization of elastic component, sensor, actuator, and energy harvesting system theoretically, which is significant and can be expected to be widely applied on mechanical systems.